2004
DOI: 10.1111/j.0002-9092.2004.00611.x
|View full text |Cite
|
Sign up to set email alerts
|

The Manure Hits the Land: Economic and Environmental Implications When Land Application of Nutrients Is Constrained

Abstract: The discharge of manure nutrients into area waters from confined animal feeding operations is considered a leading contributor to U.S. water quality impairments. An option to mitigate these impairments is to constrain land application of manure. When these constraints are particularly binding, due to minimal acceptance of manure as a substitute for commercial fertilizer, potentially large and unanticipated changes in returns to agricultural production and water quality may occur. Moreover, some of the cost of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 10 publications
0
27
0
2
Order By: Relevance
“…Farmers are widely believed to apply more fertilizer than absolutely needed to meet yield goals (Beegle, Carton, and Bailey 2000) due to factors ranging from risk aversion to scheduling rigidities to the costliness of acquiring information about soil nutrient status (see Sheriff 2005 for a review). As of 2002, 27 U.S. states required livestock producers to develop manure management plans (Kaplan, Johansson, and Peters 2004). Nationally, the recent EPA Confined Animal Feeding Operation (CAFO) rule requires all large animal operations to prepare NMPs as a component of applications for water pollution discharge permits (EPA 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Farmers are widely believed to apply more fertilizer than absolutely needed to meet yield goals (Beegle, Carton, and Bailey 2000) due to factors ranging from risk aversion to scheduling rigidities to the costliness of acquiring information about soil nutrient status (see Sheriff 2005 for a review). As of 2002, 27 U.S. states required livestock producers to develop manure management plans (Kaplan, Johansson, and Peters 2004). Nationally, the recent EPA Confined Animal Feeding Operation (CAFO) rule requires all large animal operations to prepare NMPs as a component of applications for water pollution discharge permits (EPA 2003).…”
Section: Introductionmentioning
confidence: 99%
“…When competition for spreadable cropland is 92 introduced in the regional analysis, the costs increase to 40−50% of the total net returns, not 93 including the offsetting savings from replacing commercial fertilizers (Ribaudo et al 2003). 94 Kaplan et al (2004) utilize a sector model to evaluate regional adjustments in production and 95 prices when CAFOs are required to meet nutrient standards. Whether the secondary price effects 96 are sufficient to offset the compliance costs depends on crop producers' WTAM.…”
Section: Jel Classification Code: Q53 Q58 21mentioning
confidence: 99%
“…It also becomes necessary to haul the manure longer distances from dairy locations. Work by Kaplan et al (2004) indicated that the United States Environmental Protection Agency (USEPA) land application restrictions increased production costs, creating unintended consequences on the costs of production and the rural economy. Other work by Feinerman et al (2004) suggested that while nitrogen and phosphorus regulatory standards for manure application achieved the environmental goal, these standards resulted in 5-15% welfare losses without considering the non-market value of benefits.…”
Section: Introductionmentioning
confidence: 99%